Rancang Bangun Aplikasi System Informasi Berbasis Website Human Resources Management System Dengan Menggunakan Metode Agile Pada PT. Kalimantan Anugrah Mandiri Inti - Farhansyah Putra, Andrean; Syah Rizal, Nurman; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
PT. Kalimantan Anugrah Mandiri Inti faces obstacles in managing employee data which is still done manually using Microsoft Excel software. This process is time consuming, prone to errors, and less centralized, making it difficult to recapitulate, search for data, and monitor company assets. To overcome these problems, this study aims to design and build a prototype of a web-based Human Resources Management System (HRMS) application that is able to automate employee data management, improve operational efficiency, and provide a secure and integrated system. The development of this application was carried out using the AGILE methodology, by combining observation, interviews, and literature studies to produce solutions that suit the company's needs. The designed HRMS application is expected to be able to speed up the data input process, simplify employee data management, minimize the risk of asset loss, and ensure data security and privacy. With the implementation of this system, the company can improve the efficiency of the personnel department and support better decision making.